2013
DOI: 10.18052/www.scipress.com/ilshs.5.1
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Psychological Hardiness with Work Holism

Abstract: Background and Aim: Present research intends to investigate relationship of psychological hardiness with work holism among high school teachers. Methods: The under study society includes all male and female high school teacher in Ghorveh city in the academic year 2012-2013. Using simple random sampling method, a sample size of 100 male and female teachers was selected. To collect data, Kobassa Psychological Hardiness Questionnaire and Aghabeigi Workaholics Questionnaire were employed. To analyze the data, desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…Roth, Wiebe, Fillingim, & Shay (1989, p.136) reported that life events, fitness, hardiness, and health were significantly related while hardiness was found to have stress-resistance effects. The recent empirical studies have also reported the negative correlation of high psychological hardiness with negative individual outcomes (e.g., Britt, Adler, & Bartone, 2001;Bartone, 2012;Kalantar, Khedri, Nikbakht, &Motvalian, 2013;Khaledian, Hasanvand, & Pour, 2013). Klag & Bradley (2004) found a strong relationship between stressful daily experiences and mental health problems and reported that psychological hardiness had an intervening variable role in that relationship.…”
Section: Psychological Hardiness: a Resource For Coping With Strainmentioning
confidence: 99%
“…Roth, Wiebe, Fillingim, & Shay (1989, p.136) reported that life events, fitness, hardiness, and health were significantly related while hardiness was found to have stress-resistance effects. The recent empirical studies have also reported the negative correlation of high psychological hardiness with negative individual outcomes (e.g., Britt, Adler, & Bartone, 2001;Bartone, 2012;Kalantar, Khedri, Nikbakht, &Motvalian, 2013;Khaledian, Hasanvand, & Pour, 2013). Klag & Bradley (2004) found a strong relationship between stressful daily experiences and mental health problems and reported that psychological hardiness had an intervening variable role in that relationship.…”
Section: Psychological Hardiness: a Resource For Coping With Strainmentioning
confidence: 99%
“…Here, psychological hardiness is defined as the ability to understand the external conditions accurately and to make a desirable decision about oneself (Khaledian, Hasanvand & Hassanpour, 2013). Psychological hardiness has three dimensions: commitment refers to the tendency to involve oneself in the activities in life and have a genuine interest in and curiosity about the activities, things, and other people (Kardum, Hudek-Knezevic & Krapic, 2012).…”
Section: International Journal Of Academic Research In Business and Smentioning
confidence: 99%
“…The two research studies reported here focus on the irrational beliefs of teachers, a factor that previous research with samples of teachers has shown to mediate stress (e.g., Popov and Popov 2015), psychological hardiness and emotional intelligence (Khaledian et al 2016) and teacher self-efficacy (e.g., Klassen and Chiu 2010).…”
mentioning
confidence: 99%